Birincil immün yetersizlikli hastalarda otoimmünite çeşitliliği, klinik özellikleri ve tedavi seçenekleri - (:unkn) unknown (My University, 2016)
Amaç: Birincil immün yetersizliklerle otoimmünite ilişkisi bilinmekle birlikte, son yıllarda yeni tanımlanan immün yetersizlikler nedeniyle tekrar dikkat çekici bir konu olmuştur. Buna bağlı olarak, birincil immün yetersizlikte otoimmünite gelişim mekanizmalarının ve hedefe yönelik yeni tedavi seçeneklerinin araştırılması gündeme gelmiştir. Bu çalışmada genetik tanısı olan birincil immün yetersizlikli hastalarımızda otoimmünite bulguları, çeşitliliği ve tedaviye yanıtlarının incelenmesi amaçlanmıştır.Gereç ve Yöntemler: Kliniğimizde izlenen otoimmün bulgusu olan genetik tanısı belirlenmiş birincil immün yetersizlikli hastaların dosyaları tarandı. Hastaların demografik ve klinik özellikleri ve tedavi uygulamaları değerlendirildi.Bulgular: Genetik mutasyonu tanımlanmış olan toplam 30 hastada otoimmünite bulgusu saptandı. Hastalarda ilk bulgunun ortaya çıkış yaşı ortalama 8,96±14,64 ay iken, genetik tanı alma yaşı ortalama 82,55±84,71 ay idi. Otoimmünite bulgularının en sık görüldüğü hastalıklar X'e bağlı immün disregülasyon, poliendokrinopati, enteropati sendromu (n=5, %16,7), otoimmün lenfoproliferatif sendrom (n=3, %10), lipopolysaccharide-responsive beige-like anchor protein eksikliği (n=3, %10) ve DiGeorge sendromu (n=3, %10) olarak belirlendi. On iki (%40) hastada, hastalık bulguları ilk ortaya çıktığında otoimmün bulguların olduğu görüldü. En sık saptananlar ise enflamatuar bağırsak hastalığı, enflamatuar bağırsak hastalığı benzeri bulgular (n=14, %46,7), immün trombositopenik purpura (n=11 ,%36,7) ve otoimmün hemolitik anemi idi (n=9, %30). On beş (%50) hastada immün baskılayıcı ajanlara yanıt gözlendi. On hastaya kemik iliği nakli uygulandı. Toplam altı hasta çeşitli nedenlerle yaşamını yitirdi.Çıkarımlar: Birincil immün yetersizlikli hastalarda otoimmün hastalıklar sık olarak görülmektedir. Erken başlangıçlı otommünite bulgusu gözlenen hastalarda, birincil immün yetersizlik olasılığı göz önünde bulundurulmalı ve bu hastalar immün yetersizlik gelişimi açısından dikkatle izlenmelidir. Birincil immün yetersizliğin erken tanınması sağ kalım üzerine olumlu etki sağlayacaktır.

Aim: Although the association between primary immunodeficiency and autoimmunity is already well-known, it has once again become a topic of debate with the discovery of newly-defined immunodeficiencies. Thus, investigation of the mechanisms of development of autoimmunity in primary immunodefficiency and new target-specific therapeutic options has come to the fore. In this study, we aimed to examine the clinical findings of autoimmunity, autoimmunity varieties, and treatment responses in patients who were genetically diagnosed as having primary immunodeficiency.Material and Methods: The files of patients with primary immunodeficiency who had clinical findings of autoimmunity, who were diagnosed genetically, and followed up in our clinic were investigated. The demographic and clinical features of the patients and their medical treatments were evaluated. Results: Findings of autoimmunity were found in 30 patients whose genetic mutations were identified. The mean age at the time of the first symptoms was 8.96±14.64 months, and the mean age of receiving a genetic diagnosis was 82.55±84.71 months. The most common diseases showing findings of autoimmunity included immune dysregulation, polyendocrinopathy, enteropathy X-linked syndrome (16.7%); autoimmune lymphoproliferative syndrome (10%); lipopolysaccharide-responsive beige-like anchor protein deficiency (10%); and DiGeorge syndrome (10%). Twelve (40%) patients showed findings of autoimmunity at the time of first presentation. The most common findings of autoimmunity included inflammatory bowel disease, inflammatory bowel disease-like findings (n=14, 46.7%), immune thrombocytopenic purpura (n=11, 36.7%), and autoimmune hemolytic anemia (n=9, 30.0%). A response to immunosupressive agents was observed in 15 (50%) patients. Ten patients underwent hematopoietic stem cell transplantation. Six patients were lost to follow-up due to a variety of complications.Conclusion: Autoimmunity is frequently observed in patients with primary immunodeficiency. The possibility of primary immunodeficiency should be considered in patients with early-onset manifestations of autoimmunity, and these patients should be carefully monitored in terms of immunodeficiency development. Early diagnosis of primary immunodeficiency may provide favorable outcomes in terms of survival.
The plethora, clinical manifestations and treatment options of autoimmunity in patients with primary immunodeficiency
Keywords: Hematoloji